2017
DOI: 10.1261/rna.061523.117
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of CrPV and HCV IRES-mediated eukaryotic translation using single-molecule fluorescence microscopy

Abstract: Protein synthesis is a complex multistep process involving many factors that need to interact in a coordinated manner to properly translate the messenger RNA. As translating ribosomes cannot be synchronized over many elongation cycles, single-molecule studies have been introduced to bring a deeper understanding of prokaryotic translation dynamics. Extending this approach to eukaryotic translation is very appealing, but initiation and specific labeling of the ribosomes are much more complicated. Here, we use a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…According to tRNA copy numbers for the tRNA abundance pool in CHO cell line (Genomic tRNA Database), when the position +4 mutates different nucleotide types in bicistronic reporter plasmids, the tRNA abundances for the second codon (+4XTG+6, X means any nucleotide, tRNA copy number for GTG is 9, tRNA copy number for CTG is 10, tRNA copy number for TTG is 4, tRNA copy number for ATG is 16) following the start codon have no obvious effect on mediating the EGFP gene expression levels. This result implies that nucleotide context at +4 nucleotide position might influence the local structural formation rather than tRNA abundances, leading to the changes of gene expression mediated by HCV IRES (Jaafar et al, 2016;Bugaud et al, 2017;Ma et al, 2018;Mengardi et al, 2017;Ross et al, 2017;Zhu et al, 2017). Of note, the results show that the positions -3A and +4G had a better performance in improving the translation efficiency mediated by HCV IRES than the preferred nucleotide usage bias (-3A, +4A) in the positions -3 & +4 of the translation initiation region of HCV, implying that the Kozak-like nucleotide context (-3A, +4G) probably impacts the ribosome binding to the translation initiation region of HCV.…”
Section: Discussionmentioning
confidence: 99%
“…According to tRNA copy numbers for the tRNA abundance pool in CHO cell line (Genomic tRNA Database), when the position +4 mutates different nucleotide types in bicistronic reporter plasmids, the tRNA abundances for the second codon (+4XTG+6, X means any nucleotide, tRNA copy number for GTG is 9, tRNA copy number for CTG is 10, tRNA copy number for TTG is 4, tRNA copy number for ATG is 16) following the start codon have no obvious effect on mediating the EGFP gene expression levels. This result implies that nucleotide context at +4 nucleotide position might influence the local structural formation rather than tRNA abundances, leading to the changes of gene expression mediated by HCV IRES (Jaafar et al, 2016;Bugaud et al, 2017;Ma et al, 2018;Mengardi et al, 2017;Ross et al, 2017;Zhu et al, 2017). Of note, the results show that the positions -3A and +4G had a better performance in improving the translation efficiency mediated by HCV IRES than the preferred nucleotide usage bias (-3A, +4A) in the positions -3 & +4 of the translation initiation region of HCV, implying that the Kozak-like nucleotide context (-3A, +4G) probably impacts the ribosome binding to the translation initiation region of HCV.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that transgene expression may be affected by antibiotic resistance markers 20 , 21 or choice of IRES for co-expression. 26 , 27 , 28 , 29 , 30 To investigate the effect of these factors on Tet-On system, we generated two different customized piggyBac tetracycline-inducible mCherry expression vectors, with the same construct except for their antibiotic resistance gene ( Figure 3 A), based on a vector from previous study. 11 The vectors contained a Tet-On promoter driving mCherry and a rEF1a constitutive promoter driving rtTA, which was conjugated to the neomycin (EMCV-Neo-mCherry) or puromycin resistance gene (EMCV-Puro-mCherry) with an IRES sequence form the EMCV ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…These values are much lower than those for minimal in vitro bacterial systems [∼3 s −1 at saturating TC, 25 °C ( 38 , 43 )] or for in vivo eukaryotic elongation [3 to 5 s −1 ( 44 )], likely reflecting, at least in part, the absence of eukaryotic factors essential for efficient catalysis in these minimal systems ( 39 ). Thus, for example, Bugaud et al ( 45 ) report a rate constant of ∼0.7 s −1 at ∼30 °C in a rabbit reticulocyte extract, which may contain such factors. It is not unlikely that bacterial elongation is less dependent on such additional factors.…”
Section: Discussionmentioning
confidence: 99%